Aminophthalimide as a mimetic of purines and a fluorescent RNA base surrogate for RNA imaging. Issue 15 (21st March 2023) - Lang, Fabian; Rönicke, Franziska; Wagenknecht, Hans-Achim
Abstract : Aminophthalimide and N, N -dimethylaminophthalimide are used as fluorescent mimetics of purines due to their similar size and their possibility for hydrogen bonding. Abstract : Aminophthalimide and N, N -dimethylaminophthalimide are used as fluorescent mimetics of purines due to their similar size and their possibility for hydrogen bonding. Their C-nucleotides were synthetically incorporated into RNA by means of phosphoramidite chemistry, behave as nonspecific fluorescent base analogs with flexible hydrogen bonding capabilities, and show solvatochromic fluorescence that is suitable for RNA imaging in live cells.